Local Defence (Self-Defence) in Lithuania during the Nazi German Occupation (1941–1944) - Zizas, Rimantas (Genocidas ir rezistencija, 2002)
In the summer of 1943 a substantial turning point took place in the Eastern front, the Germans lost their strategic initiative and were dislodged far to the West. Lithuania was not anymore a remote and quite country to protect their rear. In summer 1943 due to unsuccessful military and labour mobilization and spreading armed underground activities of the Soviets, the Germans consolidated the mass repressions in Lithuania, however proclaiming the locals responsible for the acts of sabotage. Trying to protect the Lithuanians both from the terror of the Soviet partisans and from the terror retaliation of the Germans, the Lithuanian self-governing administrations volunteered to form armed security units from about 30 thousand men. These units were to act under the supervision of the region authorities. During the negotiations with the Germans in the beginning of September in 1943 the principle agreements on the establishment of these units were made, however the Germans refused to arm them the Lithuanians having to equip the squads themselves. The local defence (self-defence) units as planned were to be established in villages, boroughs and towns. Their task was to protect the property and residents of the living sites", and in general they were to the fight against the banditry of the Bolshevik elements". Moreover, a separate military unit of 3 thousand was to be formed to defend the major communication roads and objects, and to support the local squads.
Keywords: German occupation; antinazi resistance; local self-defence; collaborators; Soviet partisans